Functional Organization of extraterrestrial underground base on Mars - Praslova, V.; Riabets, Y.; Shchurova, V.; Zinovieva, O.; Harbar, M. (International Journal of Innovative Technology and Exploring Engineering, 2020)
In the article relevant problems of colonization of other planets by mankind and development of extraterrestrial settlements are examined, in particular colonization of Mars and creation of Martian multifunctional base. Modern projects of leading space agencies for research and Mars colonization, shipping of equipment and the first settlers to the planet, and also projects of the first Martian habitats within the modern space technologies are discussed. In response to that natural and climatic conditions of the planet Mars which could substantially influence the formation and development of extraterrestrial multifunctional base are analyzed. Main natural and climatic factors such as high radiation background, absence of atmosphere, extreme temperature profile, low gravity, that have significant influence on formation of the Martian settlement on functional architectural and organizational levels are determined in the study. Functional model for establishment of an autonomic multifunctional base in extraterrestrial environment under the surface of the planet is proposed like the most fully satisfying the requirements for organization of extraterrestrial artificial environment for human's long-term stay considering extreme climate conditions of planet Mars and the desire to create comfortable conditions for livelihood of Martian pioneers. Basic blocks are determined and zones being parts of these blocks, which form the basis of the functional organization of extraterrestrial multifunctional complexes are detected. Possible options for functional connections between blocks and zones are analyzed.
Keywords: architecture; functional organization; extraterrestrial complexes; underground multifunctional complexes; colonization of Mars